On hilbert property of rings. - Pourtaherian, Hamideh; Rakhimov, Isamiddin S.; Sapar, Siti Hasana (Hikari Ltd, 2011)
In this paper, we study a Hilbert property with respect to the skew polynomial extensions. A property ∗ of a ring R is said to be the Hilbert property if its polynomial extension possesses the same property ∗.